Self-Confidence Characteristics in Early Childhood Education Students During Learning at School - Wardah Suweleh; Meirza Nanda Faradita (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to identify patterns of self-confidence in early childhood education students during the learning process at school and explore the gap between self-perception and actual behavior. The study used a descriptive qualitative approach with 10 students at ABA 30 Kindergarten as subjects. Data collection techniques included observation, interviews with class teachers and guidance counselors, and an open-ended questionnaire to explore students' self-perceptions. Data were analyzed through data reduction, data presentation, and conclusion drawing using triangulation of sources and techniques. The results of the study indicate that, through observation, most students still exhibit low levels of self-confidence in learning, as evidenced by hesitation in completing assignments, dependence on peers, and a lack of courage to speak or express opinions in front of the class. However, the questionnaire results indicated that the majority of students assessed themselves as having high levels of self-confidence. This finding indicates a gap between students' self-perception and actual behavior during the learning process. This gap suggests that, at this stage of early childhood development, self-evaluation does not fully reflect actual behavior in learning situations. This study contributes by showing that understanding the self-confidence of early childhood education students needs to be viewed comprehensively through a combination of observation, interview, and self-perception methods, so that teachers can design more effective learning strategies to develop students' independence and courage in learning.